'Missing Girls' in the South Caucasus Countries : Trends, Possible Causes, and Policy Options - Das Gupta, Monica (World Bank, Washington, DC, 2015)
Sex ratios at birth rose sharply in the South Caucasus countries after 1991, but recent data indicate that this trend is turning. What caused this rise, and what can be done to accelerate its normalization? Traditional kinship systems in the region are similar to those of other settings with sex-selection: structured for collaboration among male kin and dependence only on sons, not daughters. Yet it is anomalous to find sex-selection in a region that under the Soviet Union has for long been substantially urbanized and gender-equitable in public life — factors associated with declines in sex-selection elsewhere. Sex-selection manifested itself only after the sudden economic and governance meltdown following the dissolution of the Soviet Union in 1991. Jobs, basic services, and social protection mechanisms unraveled. People scrambled for coping mechanisms, and sons offer the traditional form of support under uncertainty. Basic services, pensions, and safety nets have been rebuilt, but the process involved years of policy changes. Strengthening these institutions, and maintaining credible continuity of expectations in them, is critical to accelerating normalization of sex ratios.